Inverse Kinematics Analysis and Simulation of a 5 DOF Robotic Arm using MATLAB - Abaas, Tahseen F.; Khleif, Ali A.; Abbood, Mohanad Q. (Al-Khwarizmi Engineering Journal, 2020)
Kinematics is the mechanics branch which dealswith the movement of the bodies without taking the force into account. In robots, the forward kinematics and inverse kinematics are important in determining the position and orientation of the end-effector to perform multi-tasks. This paper presented the inverse kinematics analysis for a 5 DOF robotic arm using the robotics toolbox of MATLAB and the Denavit-Hartenberg (D-H) parameters were used to represent the links and joints of the robotic arm. A geometric approach was used in the inverse kinematics solution to determine the joints angles of the robotic arm and the path of the robotic arm was divided into successive lines to accomplish the required tasks of the robotic arm.Therefore, this method can be adopted for engineering applications. MATLAB (Graphical User Interface) program was used to simulate the movement of the robotic arm in 3D. Also, MATLAB (GUI) has been used to view the position of each joint.The results showed thatthe maximum error in the x, y, and z coordinates of the end-effector were 0.0251 %, 0.0239 %, and 0.1085 % respectively.